Beyond preservation : restoring and inventing landscapes - Baldwin, A. Dwight; De Luce, Judith; Pletsch, Carl (University of Minnesota Press, 1994)
Addressing current ecological issues, from the philosophical to the practical, Frederick Turner and William R. Jordan III Here offer a new paradigm for understanding the relationship between the humans and nature. Challenging the idea that preserving nature is the only solution to environmental problems, they advocate going beyond preservation to restoration and actual construction of our landscape. Fifteen respondents reflect on the implications and consequences of Turner's and Jordan's bold proposals.Contributors include Gary W. Barrett, Ann Cline, David L. Gorchov, William Jordan III, G. St.